2022
DOI: 10.1155/2022/4782344
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia Diagnosis and Treatment: Risk Stratification in Children and Adolescents

Abstract: Dyslipidemias or dyslipoproteinemias are quantitative changes in total cholesterol concentration, respective fractions, or triglycerides in the plasma. Evidence supported that dyslipidemia in childhood is associated with atherosclerosis in adulthood, and early identification and treatment potentially reduce cardiovascular risk in adulthood, which is the principal cause of morbidity and mortality in developed countries. Dyslipidemias can result from primary lipoprotein metabolism changes due to different geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…We found that BMI-SDS was positively correlated with DHEA-SO4, HOMA-IR, and Ty-G. Corvalan et al (Corvalán et al, 2013) showed that obese children two-fold risk for highly DHEA-SO4 levels in seven years old non-obese, prepubertal children. Childhood lipid disorders are a well-known risk factor for metabolic syndrome and cardiovascular complications (Mosca et al, 2022). Dyslipidemia has been investigated in many studies in patients with PA; While some studies have found that the blood lipid profile is similar to the control group (Bezen et al, 2022;de Jesus Teixeira et al, 2004;Utriainen et al, 2007), the others showed that patients with PA have dyslipidemia (Ibáñez et al, 1998(Ibáñez et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…We found that BMI-SDS was positively correlated with DHEA-SO4, HOMA-IR, and Ty-G. Corvalan et al (Corvalán et al, 2013) showed that obese children two-fold risk for highly DHEA-SO4 levels in seven years old non-obese, prepubertal children. Childhood lipid disorders are a well-known risk factor for metabolic syndrome and cardiovascular complications (Mosca et al, 2022). Dyslipidemia has been investigated in many studies in patients with PA; While some studies have found that the blood lipid profile is similar to the control group (Bezen et al, 2022;de Jesus Teixeira et al, 2004;Utriainen et al, 2007), the others showed that patients with PA have dyslipidemia (Ibáñez et al, 1998(Ibáñez et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The data found in the in vivo and in vitro studies identified in the specialized literature regarding the effect of secondary metabolites recovered from plant waste on blood sugar variationsan important parameter in the diagnosis of diabetesare presented in Table I. Prunus tomentosaseed Aromatic glycosides [40] In an investigation carried out by [59] regarding the antiglycaemic activity have been tested in vitro the inhibitory activity of the isolated compounds against Type VI-B porcine pancreatic α-amylase (by [49]. Being a lipid metabolism disorder, it is standard diagnosticated by a lipid profile.…”
Section: Bioactive Compounds Isolated From Vegetal Waste Used In Prev...mentioning
confidence: 99%
“…Being a lipid metabolism disorder, it is standard diagnosticated by a lipid profile. At the same time, dyslipidaemia is one of the risk factors that significantly contribute to cardiovascular diseases, especially atherosclerosis [49]. Dyslipidaemia is associated with diabetes, both type I and type II [64,68], through low HDL-C, high TG and LDL-C levels.…”
Section: Bioactive Compounds Isolated From Vegetal Waste Used In Prev...mentioning
confidence: 99%
“…Dyslipidemia is a well-known risk factor for cardiovascular diseases (CVDs) [ 1 , 2 ], which constitutes the leading cause of deaths globally [ 3 ]. Dyslipidemia is defined as an imbalance in the levels of lipids in the blood and is distinguished as either primary, with genetic determination, or secondary, due to acquired conditions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is defined as an imbalance in the levels of lipids in the blood and is distinguished as either primary, with genetic determination, or secondary, due to acquired conditions [ 2 ]. This term fully expresses the most general disturbance of the metabolic balance of lipids [ 1 ]. In order to predict and diagnose dyslipidemia, there is a standard serum-based lipid profile test that includes the determination of total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), and triglyceride (TG) levels [ 4 ].…”
Section: Introductionmentioning
confidence: 99%